Innovative Teaching-Learning Method for Engineering Mathematics Through Video Lectures in Rural Areas - Hiwarekar, A.P. (Journal of Engineering Education Transformations, 2025)
Mathematics is an important subject required for the foundation and has applications in all branches of engineering. Mathematical knowledge and skills are required for higher study, developing new technology and innovations. But creating students’ interest in learning activities is always a challenging task for every mathematics teacher. Many engineering students are failing in the first year of their studies. This problem becomes more important and challenging in rural areas. There is always a concern about the problem that why students are not taking interest in learning? Out of many possible ways to deal with this problem, the use of flipped classrooms (FCR) plays an important role. This paper deals with the use of FCR for engineering students from rural areas. In addition to classroom teaching, for technology-based learning, video lectures (VLs) are provided to students of first-year engineering for the subject of engineering mathematics. Starting with a review of FCR, experimentation of VLs, and its impact on learning activities and result has been presented. Various surveys at different levels and examination results are considered for conclusions. Through this action research, we have shown that VL is one of the most useful tools for enhancing learning and improving the results of students in rural areas. It has been further shown that this method is very much accepted by students.